Review of methods and applications for promoting gas hydrate formation process - Xia, Zhiming; Zhao, Qi; Chen, Zhaoyang; Li, Xiaosen; Zhang, Yu; Xu, Chungang; Yan, Kefeng (Journal of Natural Gas Science and Engineering, 2022)
Hydrate-based application technologies have exhibited tremendous potential in terms of physical feasibility and the lower energy utilization criterion. However, it should be noted that some issues (the conditions, rate, and gas storage capability) are still significant factors to affect hydrate-based processes as future sustainable technolo-gies. The main objective of this work is to overview both the mechanism and methods for promoting hydrate formation processes, as well as the application of hydrate-based technologies, including methane or hydrogen storage and/or transport, gas (especially CO2) separation and sequestration, seawater desalination, and cold energy storage. Furthermore, the snapshots of the current state-of-the-art, opportunities for further research and development, and pathways for commercializing the hydrate-based application technologies are presented. It is evident that hydrate-based application technologies will play significant roles soon in certain areas worldwide, and have the potential to be, perhaps, more sustainable techniques than the current commercial technologies.